2013
DOI: 10.1254/jphs.13048fp
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Schisandrin B Stereoisomers on ATR-Mediated DNA Damage Checkpoint Signaling

Abstract: Abstract.We have previously reported that schisandrin B (SchB) is a specific inhibitor of ATR (ataxia telangiectasia and Rad-3-related) protein kinase. Since SchB consists of a mixture of its diastereomers gomisin N (GN) and -schisandrin (-Sch), the inhibitory action of SchB might result from a stereospecific interaction between one of the stereoisomers of SchB and ATR. Therefore, we investigated the effect of GN and -Sch on UV (UVC at 254 nm)-induced activation of DNA damage checkpoint signaling in A549 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…This apparent hepatoprotective effect is likely related to the antioxidant activity and modulation of the NFkB pathway of Sch B (34 - 36). Recently, it was found that gomisin N, the active component of Sch B, can inhibit the DNA damage checkpoint signaling by stereospecifically interacting with ataxia telangiectasia and Rad-3-related protein kinase (37). However, pro gressive increases in serum ALT and AST activities were observed in MA-treated mice from 48 to 72 h posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…This apparent hepatoprotective effect is likely related to the antioxidant activity and modulation of the NFkB pathway of Sch B (34 - 36). Recently, it was found that gomisin N, the active component of Sch B, can inhibit the DNA damage checkpoint signaling by stereospecifically interacting with ataxia telangiectasia and Rad-3-related protein kinase (37). However, pro gressive increases in serum ALT and AST activities were observed in MA-treated mice from 48 to 72 h posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated that SF extract can prevent ethanol-induced fatty liver, possibly through activation of AMPK (AMP kinase) and peroxisome proliferator-activated receptor α (PPAR α ) signaling pathway [21]. Gomisin N, a diastereomer of schisandrin B (Sch B, a major active ingredient of SF), inhibited DNA damage checkpoint signaling by stereospecifically interacting with ataxia telangiectasia and Rad-3-related (ATR) protein kinase [22]. Our previous studies have shown that SF extracts [23, 24], Sch B [25], bicycol [26], and bifendate [27] can reduce hepatic triglyceride (TG) and total cholesterol (TC) levels in hypercholesterolemic (HCL) mice.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the latent target is activated by the stimuli to react with the food factor to express a certain cellular effect. This type of action of food factors has been demonstrated in our studies of Sch Bmediated enhancement of doxorubicin (Dox) cytotoxicity in cancer cells [30,31]. The DNA damage checkpoint function is a part of the DNA damage response that is the crucial mechanism for maintaining genomic stability in cells [47].…”
Section: Strong Indirect Interaction As An Alternate Mode Of Functionmentioning
confidence: 74%
“…It prevented anti-cancer drug-induced DNA damage and chromosomal aberrations in the brain [25]. Further, it was shown that Sch B specifically inhibited ATR (ataxia-telangiectasia mutated Rad 3-related), a PI3 kinase family that plays a central role in the DNA damage checkpoint signaling pathway [30,31].…”
Section: Multi-functional Properties Of Food Factors As Moleculesmentioning
confidence: 99%